3D PRINTED BIOMATERIALS IN DENTAL AND MAXILLOFACIAL SURGERY: A COMPREHENSIVE REVIEW - Anita Pakuła; Anna Baranowska; Aleksandra Oparcik; Kinga Szyszka; Anastazja Orłowa; Kamil Turlej; Laura Kurczoba; Marta Cieślak; Klaudia Martyna Patrzykąt; Julia Pawłowska (International Journal of Innovative Technologies in Social Science, 2025)
This review provides a comprehensive and methodologically structured analysis of advancements in additive manufacturing (AM) and bioprinting for dental and maxillofacial reconstruction between 2017 and 2025. AM has become an essential component of personalised medicine, enabling the fabrication of patient‑specific implants, functional scaffolds, and biologically active constructs that enhance surgical precision and regenerative outcomes. The rapid development of titanium lattice frameworks, bioactive ceramics, biodegradable polymers, and hybrid multimaterial systems has significantly improved the biomechanical and biological performance of craniofacial reconstructions. Concurrently, innovations in bioprinting—including next‑generation bioinks, cell‑laden hydrogels, microvascularisation strategies, and tissue‑specific regeneration—have expanded the potential for restoring dental pulp, periodontal ligament, alveolar bone, and soft tissues using biologically integrated constructs. This review synthesises data from 164 peer‑reviewed publications, outlining key technological progress, material innovations, in vitro and in vivo biological responses, translational findings, and clinical outcomes. Despite substantial progress, challenges persist, including vascularisation of large constructs, long‑term immunomodulatory behaviour, standardisation of evaluation protocols, and regulatory integration into clinical practice. Future directions highlight the growing impact of AI‑assisted design, automated point‑of‑care manufacturing, and 4D dynamic biomaterials capable of functional adaptation. Overall, AM and bioprinting are positioned to become central technologies shaping the next generation of personalised maxillofacial reconstruction.